Daya Hambat Ekstrak Daun Mengkudu (Morinda citrifolia L.) terhadap Pertumbuhan Bakteri Bacillus cereus - Afifah Izzatul Zahra; Yuziani Yuziani; Mulyati Sri Rahayu (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Noni (Morinda citrifolia L.) is a plant typical of tropical regions including Indonesia, whose fruits, leaves, seeds, and roots are often used in traditional medicine, including as an antibacterial. This research was conducted to determine the inhibition zone of noni leaf extract (Morinda citrifolia L.). An inhibition test was carried out according to the Kirby-Bauer method with 4 replications on the growth of Bacillus cereus. The results of this study showed that a concentration of 25% produced an average inhibition zone of 9.075 mm, a concentration of 50% produced an average inhibition zone of 8.650 mm, a concentration of 75% produced an average inhibition zone of 9.275 mm, a concentration of 100% produced an average inhibition zone of 10,050 mm, positive control using ciprofloxacin produced an average inhibition zone of 30.475 mm and negative control using DMSO produced an average inhibition zone of 0.000 mm. The results of the comparative test using the Kruskal-Wallis statistical test with a p. value of 0.003 (p<0.005) and the results of the Mann-Whitney test showed that there was a significant difference between P2 and P4 with a value of 0.042 (p<0.005). The conclusion obtained from this study was that the noni leaf extract had a weak zone of inhibition on the growth of Bacillus cereus at a concentration of 100% according to Greenwood's criteria.